Mrs. Porter calling : a novel - Pearce, A. J. (Amanda-Jane) (New York : Scribner, 2023)
London, April 1943. A little over a year since she married Captain Charles Mayhew and he went away to war, Emmy Lake is now in charge of "Yours Cheerfully," the advice column in Woman's Friend magazine. Emmy is dedicated to helping readers face the increasing challenges brought about by over three years of war. The postbags are full and Woman's Friend is thriving. When socialite the Honorable Mrs. Cressida Porter becomes the new publisher of the magazine, she fills the pages with expensive clothes and frivolous articles about her friends, aided by Mrs. Pye, a Paris-obsessed fashion editor with delusions of grandeur. When it is announced that the "Yours Cheerfully" column will be cut, Emmy and her friends must find a way to save the magazine that they love--Adapted from jacket.
Keywords: Women journalists -- England -- London -- Fiction; Journalists -- Fiction; Advice columnists -- Fiction; World War, 1939-1945 -- England -- London -- Fiction; Friendship -- Fiction; Periodicals -- Fiction; Socialites -- Fiction; England -- Fiction; London (England) -- Fiction; Historical fiction